Energy Consumption and Nutritional to Status Emotional Eating Behavior Among Pregnant Women in Malang, Indonesia - Nashih, Nadia Fauziyah; Paramita, Farah; Kurniawan, Agung; Santre, Siriporn; Nasih, Ahmad Munjin (Jurnal Kesehatan Masyarakat, 2024)
Emotional eating behavior and increased food intake during emotional conditions are some factors that can contribute to obesity in pregnant women. This study examined the relationship between emotional eating behavior with energy consumption and nutritional status of pregnant women. This study was conducted from January to March 2024 and used an analytical observational method with a cross-sectional study. The subjects were 59 pregnant women in the second and third trimesters at Kedungkandang Community Health Center, Malang, Indonesia. Emotional eating, energy consumption, and nutritional status was tested with correlation rank spearman test. In this study, 45.7% of respondents were high emotional eaters, 40.7% had sufficient energy intake, and 72.9% had a normal nutritional status. Spearman correlation test showed p0.05 for energy consumption (p=0.008) and p0.05 for nutritional status (p=0.548). We concluded that emotional eating behavior has a significant relationship with energy consumption but has no relationship with nutritional status. It is important to consider the larger context in which emotional eating behaviors take place to comprehend nutritional status during pregnancy. Therefore, future studies should examine other different populations or areas.